Application and role of anthropological research in the practice of forensic medicine - Kósa, Ferenc (Acta Biologica Szegediensis, 2000)
Whereas in anthropology the application of the new methods is predominantly taken at random and is characteristic of basic research, in forensic medicine the objectives, motives and results of osteological research are of prime interest, due to its role in criminology and administration of justice. Because of the significance of professional assessments in judicial verdicts, it demands the application of the most modern methods of analysis that can later on be recommended as practical methods used in both palaeoanthropological analyses and research work. With his scientific achievements the author indicates how the forensic medical profession promoted historical anthropological research and in return how classical anthropology (anthropometry) promoted forensic medical expertise work, among others the identification of skeletons of unknown origin, and also how scientific achievements can mutually be used for the benefit of the development of both fields.